The Study of the Influence of Lao Zi's Philosophy on Chinese Calligraphy Art (Journal of Global Arts Studies, 2023)
Background: With the increasing spread and influence of Chinese traditional culture in the world, Lao Tzu's philosophy, as one of its core ideas, has an increasingly profound influence on the art of calligraphy. Objective: This study aims to explore the influence of Laozi's philosophy on Chinese calligraphy art, and to analyze its enlightenment and guidance in calligraphy creation and artistic expression. Medhoes: The study used literature research, cultural and historical investigation, case study and expert interviews. Results: The results show that Laozi philosophy is embodied in the aesthetic concept of Chinese calligraphy art as pursuing the common beauty of natural and natural flow, emphasizing the combination of virtual and real, vivid artistic expression, as well as the unity of artistic conception and ink. In the aspect of calligraphy creation, Laozi's philosophy encourages artists to explore themselves, emphasizes the adjustment and purification of mood and creative realm, and advocates the artistic pursuit of reducing the road and simplifying the complex. The analysis of classical calligraphy works and the calligraphers 'quotation and integration of Laozi's philosophy show that Laozi's philosophy has a profound influence on the art of calligraphy. Conclusion: The conclusion is that Lao Tzu's philosophy provides the theoretical basis and aesthetic guidance for Chinese calligraphy art, and has an important enlightenment and guiding role for the creative practice of calligraphy artists. Future research can deepen the understanding of the influence of Lao Tzu's philosophy on calligraphy art and other art fields in the context of globalization.
Keywords: Lao Tzu philosophy; Chinese calligraphy art; aesthetic concept; artistic expression